Membaca Ulang Status Paulus Dalam 1 Korintus 7:7-9: Perspektif Biblika Terhadap Pria Lajang Dalam Masyarakat Batak Toba - Marlon Butar-Butar; Sri Wahyuni (Institut Agama Kristen Negeri (IAKN) Ambon, 2024)
This article originates from the social and cultural challenges faced by single men in Batak Toba society, where marriage is considered an essential part of the Dalihan Na Tolu social structure. A man's failure to marry is often perceived as a life failure and a hindrance to his role in traditional customs. The research problem addressed in this study is how Paul's status as a single man in 1 Corinthians 7:7-9 can provide new meaning for single Batak men in dealing with social and cultural pressures. This study employs a qualitative method with a hermeneutic approach to analyze the biblical text and its interaction with Batak cultural realities. The findings reveal that Paul's status as a single man is not a form of failure but rather a special calling with significant theological and practical value. Therefore, the understanding of single men's status in the Batak context can be reconstructed through a broader theological perspective and a more open dialogue between culture and Christianity